(untitled) (AYUSHDHARA, 2024)
In Ayurveda, infertility is addressed under the concept known as "Bandhyatava," which is described in ancient texts such as Charak Samhita, Sushrut Samhita, Ras Ratna Samuchya, and Harit Samhita. Acharya Sushrut described four crucial factors for fertility: Ritu (menstruation), Kshetra (functioning reproductive organs), Ambu (digestive juices) and Beej (healthy sperm and ovum). It occurs due to the vitiation of Vata dosha where Kapha dosha also contributes to the formation of blockage. Beeja Grahana is unable due to Sanga Strotodushti of Artavavaha i.e., tubal blockage which leads to failure of conception. Fallopian tube is an essential part of the Artavavaha Srotas as the Beej Samagam (ovum and sperm) takes place here. In the current case scenario, Bandhyatva is due to Tubal Blockage. A 37-year-old female patient was reported to PTSR OPD with the complaints of irregular menses with decreased duration and wants to conceive irrespective of unprotected sexual intercourse since 3 years. Her HSG scan suggestive of B/L fallopian tube cornual blockage. Aims and Objectives: To maintain the balance between the four factors to conceive through Sanshodhan therapy. Patients has been treated with Sanshodhan Karma followed by 3 consecutive cycles of Sahacharadi Taila Uttarbasti and 3 cycles of Phalghrita Uttarbasti along with Shaman Chikitsa. Results: After completion of treatment Bilateral Tubes were patent observed in Sonohysterosalpingography. Conclusion: This case study found that the treatment administered was highly effective in addressing infertility caused by tubal blockage.